Dancing science - Beattle, Sally; Hampshire Dance ([Australia : Hampshire Dance, 2007)
Dancing science is a teachingresource packed, aimed at young people with highly effective, practical dance ideas that can assist with the delivery of the key stage 2 science curriculum in an innovative and creative way
Title from title screen
Title from container
System requirements: Microsoft Windows 98 or later; 600 MHZ Pentium III Processor; 128 MB RAM; 16x CD-ROM; 800x600 display; adobe reader
Keywords: Dance -- Study and teaching (Elementary) -- Great Britain; Science -- Study and teaching (Elementary) -- Great Britain